2020
DOI: 10.1101/2020.03.26.20044487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-host Modelling of COVID-19 in Humans

Abstract: 1COVID-19 pandemic has underlined the impact of emergent pathogens as a major threat for human 2 health. The development of quantitative approaches to advance comprehension of the current outbreak 3 is urgently needed to tackle this severe disease. In this work, several mathematical models are proposed 4 to represent SARS-CoV-2 dynamics in infected patients. Considering different starting times of 5 infection, parameters sets that represent infectivity of SARS-CoV-2 are computed and compared with 6 other viral… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 56 publications
0
51
1
Order By: Relevance
“…However, CoVID-19 rarely results in notable symptoms of upper respiratory tract infection (e.g., rhinorrhea, sneezing, or sore throat), which are commonly manifested in SARS and MERS. Some CoVID-19 patients even manifest no apparent respiratory symptoms at onset, which never occurred in SARS and MERS (24)(25)(26). Mathematical models have revealed that the 2019-nCoV virus may replicate very slowly in the first days after infection and that it could be below detection levels during the first four days post infection (26).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CoVID-19 rarely results in notable symptoms of upper respiratory tract infection (e.g., rhinorrhea, sneezing, or sore throat), which are commonly manifested in SARS and MERS. Some CoVID-19 patients even manifest no apparent respiratory symptoms at onset, which never occurred in SARS and MERS (24)(25)(26). Mathematical models have revealed that the 2019-nCoV virus may replicate very slowly in the first days after infection and that it could be below detection levels during the first four days post infection (26).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Patients infected by 2019-nCoV, similar to SARS cases, mostly present with non-specific symptoms such as fever, dry cough, and dyspnoea, or, in some cases, no evident symptoms, at the early phase of the disease (9,16,(23)(24)(25)(26)(27)48). Hence, it is a challenging task for health care professionals in the northern hemisphere to distinguish early 2019-nCoV infection from influenza and other respiratory viral infections in the seasons of winter and spring when respiratory diseases frequently break out (48).…”
Section: Infection Control and Personal Protectionmentioning
confidence: 99%
“…Tocilizumab) and immunoglobulin therapy, among others. Recently, Hernandez-Vargas & Velasco-Hernandez, 2020 proposed different intra-host mathematical models (2 based on target cell-limited model, with and without latent phase, and another considering immune response) for 9 patients with COVID-19. Numerical results in Hernandez-Vargas & Velasco-Hernandez, 2020 showed intra-host reproductive number values consistent to influenza infection (1.7-5.35).…”
Section: Introductionmentioning
confidence: 99%
“…Although models in Hernandez-Vargas & Velasco-Hernandez, 2020 have been fitted to COVID-19 patients data, a control theoretical approach is needed to characterize the model dynamics. Even when the equilibrium states are known, a formal stability analysis is needed to understand the model behavior and, mainly, to design efficient control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The viral load is one of the primary predictors of the disease progression in most infectious diseases. Mathematical models that track the viral kinetics in CoVID-19 patients have also been built recently 45 . However, very few models exist so far that incorporate the interactions of the virally infected cells with different types of immune responses in the body 28,46 .…”
Section: How Can Mathematical Models Be Used To Understand the Crosstmentioning
confidence: 99%